Understanding the macroinvertebrates of the Eastern Cordillera, in the Colombian provinces of Márquez and Lengupá (2021)
Macroinvertebrates are very important organisms in aquatic environments. They are responsible for the circulation of autochthonous organic matter from algae and non-native species in the basin and used in the biomonitoring of rivers and lakes. In order to determine the amount of deterioration in aquatic ecosystems and their importance in monitoring water quality, ten water samples were taken from different streams belonging to the provinces of Márquez and Lengupá located in the Eastern Cordillera of Colombia. This provided a very representative view of the community of different types of macroinvertebrates in the area. Additionally, the study was aimed at understanding their importance through their life cycle as well as taking into account various diagnostic characteristics to help identify issues.